Analyzing Customer Loyalty towards Zoom: The Role of Service Quality, Customer Trust, and Customer Satisfaction - Nurhayati, Dwi; Lestari, Nurfarahim Sugih (Jurnal Wacana Ekonomi, 2024)
Customer loyalty is analyzed through the roles of service quality, consumer trust, and consumer satisfaction. The research method utilized in this study is an explanatory survey research that employs a data collection technique using questionnaires and observation. The population and sample of this study are Zoom application users in the Garut district. Data analysis techniques use Structural Equation Modeling (SEM) with SmartPLS-3.0. Our findings indicate that i) all variables are in the excellent category, ii) service quality, consumer trust, and consumer satisfaction have a positive and significant effect on customer loyalty, iii) customer satisfaction can act as a mediating variable between service quality and consumer trust variables on customer loyalty. This indicates that Zoom application companies must continue to strive to maintain and improve innovation in available service features. Keywords: Customer loyalty, consumer satisfaction, service quality, consumer trust, dan Zoom.